Tourism competitiveness: bibliometric analysis of global scientific production from 1991 to 2018 - Pérez Romero, Miriam Edith; Flores-Romero, Martha Beatriz; Alfaro-García, Víctor G.; Merigó, José M. (Unidad Editorial UPTC, 2021)
In recent years, an increasing number of studies with a focus on competitiveness and economic sectors have been developed. One of them is tourism competitiveness, also known as tourism destination competitiveness and destination competitiveness. Despite the increasing interest and number of studies in this regard, little can be found about tourism competitiveness using bibliometric methods and techniques. The aim of this paper is to use bibliometric tools to examine the evolution of scientific production on the subject of tourism competitiveness. The information in this paper comes from the Web of Science scientific database. The findings demonstrate how far the research has progressed and how influential it has been in the scientific community. In the years 1991 to 2018, a total of 1,325 papers were recovered. Years, citations, writers, universities, countries, journals, and research areas are conveniently organized and presented form the systematically gathered area. Keywords: tourism competitiveness, tourism destination competitiveness, destination competitiveness, bibliometric analysis JEL Codes: L83, Z32, M10 Received: 21/07/2020.  Accepted: 08/01/2021.  Published: 01/06/2021.